Nanometer copper conductive ink, preparation method and application thereof

CN120365798BActive Publication Date: 2026-10-16DONG GUAN YUE WAH CIRCUITS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510797344.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2026-10-16
Estimated Expiration
2045-06-16

AI Technical Summary

Technical Problem

分散剂蒸发过程中会产生大量气泡,气泡的破裂会导致纳米铜颗粒之间产生较大的间隙,导致纳米铜堆积形成的电路的导电性降低;同时存在这种缺陷的电路在受到拉伸和弯曲等作用时,容易发生开裂,导致电路开路

Benefits of technology

[0017] The above application method involves sintering in two stages. The first stage (T1-T2) allows the dispersant to evaporate smoothly, reducing the formation of large pores. The second stage (20-40°C above T2) allows the molten alloy to fully fill the pores, thereby reducing the resistance of the conductive film.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to a kind of nano copper conductive ink and its preparation method and application.Nano copper conductive ink, comprising: nano copper particles, repair particles, dispersing agent, antioxidant and solvent, the boiling point of the dispersing agent is T1, the melting point of the repair particles is T2, T1 < T2 < 250 DEG C, the repair particles comprise Sn.The scheme can avoid the reduction of the conductivity of the conductive film by introducing Sn-containing repair particles into the nano copper conductive ink and using dispersing agent with boiling point lower than the melting point of the repair particles, and also improves the mechanical strength of the conductive film, prevents cracking when bending or stretching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nano-copper conductive ink, and in particular to a nano-copper conductive ink, its preparation method, and its application. Background Technology

[0002] Traditional etching methods for printing circuits not only result in significant material waste but also involve complex processes and severe environmental pollution. Printed electronics technology, an advanced circuit printing method, relies heavily on the application of conductive inks. Nano-silver conductive inks are widely used; however, silver's high cost as a precious metal limits their application. Copper, with its excellent conductivity and low cost, offers a significant cost-reduction advantage when used instead of silver in conductive ink production. However, nano-copper conductive inks still face several unresolved issues. Dispersants are required to prevent agglomeration of nano-copper particles, but these dispersants adhering to the surface of the nano-copper particles can hinder the formation of conductive pathways between particles. Therefore, sintering is necessary to remove the dispersant from the conductive film printed with nano-copper conductive ink. The evaporation of the dispersant generates numerous bubbles, and the bursting of these bubbles creates large gaps between the nano-copper particles, reducing the conductivity of circuits formed by nano-copper aggregation. Furthermore, circuits with this defect are prone to cracking under stretching and bending, leading to open circuits. Reducing the dispersant content can decrease bubble generation, but this increases the probability of nano-copper agglomeration. CN106366769A discloses an antioxidant nano-copper conductive ink, its preparation method, and its printing application. It reduces the problem of reduced conductivity caused by defects by continuously printing 50 layers, but this increases the manufacturing cost and time.

[0003] Therefore, it is necessary to propose a nano-copper conductive ink, its preparation method, and its application. Summary of the Invention

[0004] Therefore, it is necessary to propose a nano-copper conductive ink, its preparation method, and its application.

[0005] The first aspect of the present invention provides a nano-copper conductive ink, comprising: nano-copper particles, repair particles, a dispersant, an antioxidant, and a solvent, wherein the boiling point of the dispersant is T1, the melting point of the repair particles is T2, T1 < T2 < 250°C, and the repair particles contain Sn.

[0006] This solution introduces Sn-containing repair particles into the nano-copper conductive ink and uses a dispersant with a boiling point lower than the melting point of the repair particles. When the ink is printed onto the substrate to form a conductive film, and the conductive film is sintered, the dispersant evaporates when the temperature of the conductive film reaches between T1 and T2, thereby forming larger pores between the nano-copper particles. As the temperature of the conductive film further increases to T2-250℃, the repair particles transform into a molten state and can fill the pores formed by the evaporation of the dispersant through capillary action and react with the exposed surface of the nano-copper particles to form intermetallic compounds. This connects multiple non-contact nano-copper particles, thereby avoiding a decrease in the conductivity of the conductive film and also improving the mechanical strength of the conductive film, preventing it from cracking when bent or stretched.

[0007] Furthermore, the repair particles are Sn-Ag-Cu alloys. Sn-Ag-Cu alloys have a melting point between 210-220°C. For example, a Sn-Ag-Cu alloy with 96.5% Sn, 3% silver, and 0.5% copper has a melting point of 217°C. This alloy has low surface tension in the molten state, allowing it to efficiently fill pores through capillary action. Simultaneously, it can form intermetallic compounds with nano-copper, enhancing interfacial bonding and preventing the conductive film from opening during bending.

[0008] Furthermore, the particle size of the repair particles is smaller than that of the copper nanoparticles. Smaller particle size allows the repair particles to better embed themselves within the gaps between the copper nanoparticles, thus enhancing their repair effect.

[0009] Furthermore, the ratio of the particle size of the repair particles to the particle size of the nano-copper particles is 1:(2-5). This ratio can achieve a better repair effect, thereby giving the conductive film better conductivity.

[0010] Furthermore, the dispersant is polyvinylpyrrolidone (PVP). As a macromolecular dispersant, PPVP can better disperse copper nanoparticles.

[0011] Furthermore, the solvent comprises at least one of ethanol, ethylene glycol, and water.

[0012] Furthermore, the antioxidant includes ascorbic acid. Ascorbic acid can reduce Cu2+, preventing the formation of an oxide layer on the surface of the nano-copper.

[0013] Furthermore, by weight, it contains 35-45 parts of nano-copper particles, 0.5-1 parts of repair particles, 1-3 parts of dispersant, and 5-10 parts of antioxidant. If the proportion of repair particles is too low, the repair effect will be insignificant; if the proportion of repair particles is too high, it will lead to an increase in the resistance of the conductive film.

[0014] The second aspect of this application provides a method for preparing the above-mentioned nano-copper conductive ink, comprising the following steps: adding the nano-copper particles and dispersant to the solvent, stirring evenly, then adding the repair particles, ultrasonically treating for 10-20 minutes, adding the antioxidant, continuing to stir evenly, and allowing to stand to obtain the nano-copper conductive ink.

[0015] First, disperse the nano-copper, then add the repair particles ultrasonically to avoid the aggregation of small particles; finally, add ascorbic acid to prevent the reducing agent from being consumed too early, thus improving the stability of the process.

[0016] The third aspect of this application provides the application of the above-mentioned nano-copper conductive ink, which includes the following steps: printing the nano-copper conductive ink onto a substrate to form a conductive film, sintering it at T1-T2 for 5-10 minutes in an inert atmosphere, and then continuing to sinter it at 20-40°C above T2 for 10-20 minutes.

[0017] The above application method involves sintering in two stages. The first stage (T1-T2) allows the dispersant to evaporate smoothly, reducing the formation of large pores. The second stage (20-40°C above T2) allows the molten alloy to fully fill the pores, thereby reducing the resistance of the conductive film. Detailed Implementation

[0018] To facilitate understanding of this application, a more complete description will be provided below. This application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.

[0019] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of the application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified. In the description of this application, "several" means at least one, such as one, two, etc., unless otherwise explicitly specified.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0021] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0022] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0023] Unless otherwise specified, the percentage content mentioned in this application refers to mass percentage for solid-liquid mixtures and solid-phase-solid mixtures, and volume percentage for liquid-phase-liquid mixtures.

[0024] Unless otherwise specified, all percentage concentrations mentioned in this application refer to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of that component.

[0025] Unless otherwise specified, the temperature parameters in this application may be either constant temperature processing or processing within a certain temperature range. The constant temperature processing allows for temperature fluctuations within the precision range controlled by the instrument.

[0026] The term "particle" as used in this application, or a substance with a defined particle size distribution, is not necessarily spherical in shape; it may be irregular and can be either primary or secondary particles. The particle size of irregular particles is calculated as the average of their maximum and minimum diameters.

[0027] Example 1: This example provides a nano-copper conductive ink, its preparation method, and its application.

[0028] Ink formulation: 40 parts of nano copper particles (average particle size 80nm), 0.8 parts of repair particles (Sn96.5Ag3Cu0.5 alloy, average particle size 20nm, melting point 217℃), 2 parts of dispersant polyvinylpyrrolidone, 8 parts of antioxidant ascorbic acid, and 50 parts of solvent (ethanol:water = 3:1, volume ratio).

[0029] Preparation method: Add the nano-copper particles and dispersant to the solvent and stir magnetically (600 rpm, 30 min); then add the repair particles and sonicate (40 kHz, 15 min); finally add the antioxidant and continue stirring (300 rpm, 10 min). After standing and defoaming, the nano-copper conductive ink is obtained.

[0030] Application: The above ink is screen-printed onto a polyimide substrate to form a conductive film with a thickness of 50 μm and a linewidth of 100 μm. The substrate is then sintered in an inert atmosphere, first at 200°C for 8 min, then at 240°C for 15 min. After cooling, the preparation of the conductive film is complete.

[0031] Example 2: This example provides a nano-copper conductive ink, its preparation method, and its application.

[0032] Ink formulation: 40 parts of nano copper particles (average particle size 80nm), 0.5 parts of repair particles (Sn96.5Ag3Cu0.5 alloy, average particle size 20nm), 2 parts of dispersant polyvinylpyrrolidone, 8 parts of antioxidant ascorbic acid, and 50 parts of solvent (ethanol:water = 3:1, volume ratio).

[0033] Preparation method: Add the nano-copper particles and dispersant to the solvent and stir magnetically (600 rpm, 30 min); then add the repair particles and sonicate (40 kHz, 15 min); finally add the antioxidant and continue stirring (300 rpm, 10 min). After standing and defoaming, the nano-copper conductive ink is obtained.

[0034] Application: The above ink is screen-printed onto a polyimide substrate to form a conductive film with a thickness of 50 μm and a linewidth of 100 μm. The substrate is then sintered in an inert atmosphere, first at 200°C for 8 min, then at 240°C for 15 min. After cooling, the preparation of the conductive film is complete.

[0035] Example 3: This example provides a nano-copper conductive ink, its preparation method, and its application.

[0036] Ink formulation: 40 parts of nano copper particles (average particle size 80nm), 1 part of repair particles (Sn96.5Ag3Cu0.5 alloy, average particle size 20nm), 2 parts of dispersant polyvinylpyrrolidone, 8 parts of antioxidant ascorbic acid, and 50 parts of solvent (ethanol:water = 3:1, volume ratio).

[0037] Preparation method: Add the nano-copper particles and dispersant to the solvent and stir magnetically (600 rpm, 30 min); then add the repair particles and sonicate (40 kHz, 15 min); finally add the antioxidant and continue stirring (300 rpm, 10 min). After standing and defoaming, the nano-copper conductive ink is obtained.

[0038] Application: The above ink is screen-printed onto a polyimide substrate to form a conductive film with a thickness of 50 μm and a linewidth of 100 μm. The substrate is then sintered in an inert atmosphere, first at 200°C for 8 min, then at 240°C for 15 min. After cooling, the preparation of the conductive film is complete.

[0039] Example 4: This example provides a nano-copper conductive ink, its preparation method, and its application.

[0040] Ink formulation: 40 parts of nano copper particles (average particle size 80nm), 0.8 parts of repair particles (Sn96.5Ag3Cu0.5 alloy, average particle size 40nm), 2 parts of dispersant polyvinylpyrrolidone, 8 parts of antioxidant ascorbic acid, and 50 parts of solvent (ethanol:water = 3:1, volume ratio).

[0041] Preparation method: Add the nano-copper particles and dispersant to the solvent and stir magnetically (600 rpm, 30 min); then add the repair particles and sonicate (40 kHz, 15 min); finally add the antioxidant and continue stirring (300 rpm, 10 min). After standing and defoaming, the nano-copper conductive ink is obtained.

[0042] Application: The above ink is screen-printed onto a polyimide substrate to form a conductive film with a thickness of 50 μm and a linewidth of 100 μm. The substrate is then sintered in an inert atmosphere, first at 200°C for 8 min, then at 240°C for 15 min. After cooling, the preparation of the conductive film is complete.

[0043] Example 5: This example provides a nano-copper conductive ink, its preparation method, and its application.

[0044] Ink formulation: 40 parts of nano copper particles (average particle size 100nm), 0.8 parts of repair particles (Sn96.5Ag3Cu0.5 alloy, average particle size 20nm), 2 parts of dispersant polyvinylpyrrolidone, 8 parts of antioxidant ascorbic acid, and 50 parts of solvent (ethanol:water = 3:1, volume ratio).

[0045] Preparation method: Add the nano-copper particles and dispersant to the solvent and stir magnetically (600 rpm, 30 min); then add the repair particles and sonicate (40 kHz, 15 min); finally add the antioxidant and continue stirring (300 rpm, 10 min). After standing and defoaming, the nano-copper conductive ink is obtained.

[0046] Application: The above ink is screen-printed onto a polyimide substrate to form a conductive film with a thickness of 50 μm and a linewidth of 100 μm. The substrate is then sintered in an inert atmosphere, first at 200°C for 8 min, then at 240°C for 15 min. After cooling, the preparation of the conductive film is complete.

[0047] Example 6: This example provides a nano-copper conductive ink, its preparation method, and its application.

[0048] Ink formulation: 40 parts of nano copper particles (average particle size 80nm), 0.8 parts of repair particles (Sn96.5Ag3Cu0.5 alloy, average particle size 20nm), 2 parts of dispersant polyvinylpyrrolidone, 8 parts of antioxidant ascorbic acid, and 50 parts of solvent (ethanol:water = 3:1, volume ratio).

[0049] Preparation method: Add the nano-copper particles and dispersant to the solvent and stir magnetically (600 rpm, 30 min); then add the repair particles and sonicate (40 kHz, 15 min); finally add the antioxidant and continue stirring (300 rpm, 10 min). After standing and defoaming, the nano-copper conductive ink is obtained.

[0050] Application: The above ink is screen-printed onto a polyimide substrate to form a conductive film with a thickness of 50 μm and a linewidth of 100 μm. The substrate is then sintered in an inert atmosphere, first at 200°C for 8 min, then at 260°C for 15 min. After cooling, the preparation of the conductive film is complete.

[0051] Example 7: This example provides a nano-copper conductive ink, its preparation method, and its application.

[0052] Ink formulation: 45 parts of nano copper particles (average particle size 80nm), 0.8 parts of repair particles (Sn96.5Ag3Cu0.5 alloy, average particle size 20nm), 1 part of dispersant polyvinylpyrrolidone, 8 parts of antioxidant ascorbic acid, and 50 parts of solvent (ethanol:water = 3:1, volume ratio).

[0053] Preparation method: Add the nano-copper particles and dispersant to the solvent and stir magnetically (600 rpm, 30 min); then add the repair particles and sonicate (40 kHz, 15 min); finally add the antioxidant and continue stirring (300 rpm, 10 min). After standing and defoaming, the nano-copper conductive ink is obtained.

[0054] Application: The above ink is screen-printed onto a polyimide substrate to form a conductive film with a thickness of 50 μm and a linewidth of 100 μm. The substrate is then sintered in an inert atmosphere, first at 200°C for 8 min, then at 240°C for 15 min. After cooling, the preparation of the conductive film is complete.

[0055] Example 8: This example provides a nano-copper conductive ink, its preparation method, and its application.

[0056] Ink formulation: 40 parts of nano copper particles (average particle size 80nm), 0.8 parts of repair particles (Sn96.5Ag3Cu0.5 alloy, average particle size 20nm), 2 parts of dispersant polyvinylpyrrolidone, 5 parts of antioxidant ascorbic acid, and 50 parts of solvent (ethanol:water = 3:1, volume ratio).

[0057] Preparation method: Add the nano-copper particles and dispersant to the solvent and stir magnetically (600 rpm, 30 min); then add the repair particles and sonicate (40 kHz, 15 min); finally add the antioxidant and continue stirring (300 rpm, 10 min). After standing and defoaming, the nano-copper conductive ink is obtained.

[0058] Application: The above ink is screen-printed onto a polyimide substrate to form a conductive film with a thickness of 50 μm and a linewidth of 100 μm. The substrate is then sintered in an inert atmosphere, first at 200°C for 8 min, then at 240°C for 15 min. After cooling, the preparation of the conductive film is complete.

[0059] Comparative Example 1: This embodiment provides a nano-copper conductive ink, its preparation method, and its application.

[0060] Ink formulation: 40 parts of nano copper particles (average particle size 80nm), 2 parts of dispersant polyvinylpyrrolidone, 8 parts of antioxidant ascorbic acid, and 50 parts of solvent (ethanol:water = 3:1, volume ratio).

[0061] Preparation method: Add the nano-copper particles and dispersant to the solvent and stir magnetically (600 rpm, 30 min); then sonicate (40 kHz, 15 min); finally add the antioxidant and continue stirring (300 rpm, 10 min). After standing and defoaming, the nano-copper conductive ink is obtained.

[0062] Application: The above ink is screen-printed onto a polyimide substrate to form a conductive film with a thickness of 50 μm and a linewidth of 100 μm. The substrate is then sintered in an inert atmosphere, first at 200°C for 8 min, then at 240°C for 15 min. After cooling, the preparation of the conductive film is complete.

[0063] Comparative Example 2: This embodiment provides a nano-copper conductive ink, its preparation method, and its application.

[0064] Ink formulation: 40 parts of nano copper particles (average particle size 80nm), 0.8 parts of repair particles (Sn-58Bi eutectic alloy, average particle size 20nm, melting point 138℃), 2 parts of dispersant polyvinylpyrrolidone, 8 parts of antioxidant ascorbic acid, and 50 parts of solvent (ethanol:water = 3:1, volume ratio).

[0065] Preparation method: Add the nano-copper particles and dispersant to the solvent and stir magnetically (600 rpm, 30 min); then add the repair particles and sonicate (40 kHz, 15 min); finally add the antioxidant and continue stirring (300 rpm, 10 min). After standing and defoaming, the nano-copper conductive ink is obtained.

[0066] Application: The above ink is screen-printed onto a polyimide substrate to form a conductive film with a thickness of 50 μm and a linewidth of 100 μm. The substrate is then sintered in an inert atmosphere, first at 200°C for 8 min, then at 240°C for 15 min. After cooling, the preparation of the conductive film is complete.

[0067] Performance tests were conducted on the above embodiments and comparative examples: the resistance of the sintered conductive film was tested using the four-probe method; the flexible substrate was tested using a dynamic bending tester, with a 100mm*10mm substrate tested at a bending radius of 3mm, and the resistance value was measured in real time. When the resistance value change rate was >10% or suddenly turned into an open circuit, the test was stopped and the number of bending failures was recorded. The experiment was repeated 10 times and the average value was recorded.

[0068] Table 1 shows the results of resistance and bending failure times for the examples and comparative examples.

[0069] Example 1 2.45 >10000 Example 2 4.21 >10000 Example 3 3.86 >10000 Example 4 4.56 >10000 Example 5 3.52 >10000 Example 6 2.78 >10000 Example 7 4.24 >10000 Example 8 3.96 >10000 Comparative Example 1 6.54 854 Comparative Example 2 7.31 795

[0070] According to the data in Table 1, the results of Examples 1-8 are better than those of Comparative Examples 1-2. This shows that the present solution introduces Sn-containing repair particles into the nano-copper conductive ink and uses a dispersant with a boiling point lower than the melting point of the repair particles. When the ink is printed onto the substrate to form a conductive film, and the conductive film is sintered, when the temperature of the conductive film reaches between T1 and T2, the dispersant evaporates, thereby forming larger pores between the nano-copper particles. As the temperature of the conductive film further increases to T2-250℃, the repair particles transform into a molten state and can fill the pores formed by the evaporation of the dispersant through capillary action and react with the exposed surface of the nano-copper particles to form intermetallic compounds, thereby connecting multiple non-contact nano-copper particles. This avoids the reduction of conductivity of the conductive film and also improves the mechanical strength of the conductive film, preventing it from cracking when bent or stretched. Comparative Example 1, lacking repair particles, failed to repair the pores. Comparative Example 2 used a metal with a lower melting point as the repair particles; however, when the dispersant evaporated, the repair particles had already turned into a liquid state and were carried away from the pores by the gas, failing to perform their repair function, and some conductive films even experienced short circuits. Example 4 used larger-diameter repair particles, which, after melting, were difficult to penetrate into the gaps between copper particles. Example 7 used less dispersant, resulting in poor dispersion of the nano-copper, which also affected the resistivity.

[0071] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0072] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A nano-copper conductive ink, characterized in that, By weight, it contains 35-45 parts of nano copper particles, 0.5-1 parts of repair particles, 1-3 parts of dispersant and 5-10 parts of antioxidant, as well as solvent; The repair particles are Sn-Ag-Cu alloys, and the particle size of the repair particles is smaller than that of the nano-copper particles. The ratio of the particle size of the repair particles to that of the nano-copper particles is 1:(2-5). The boiling point of the dispersant is T1, and the melting point of the repair particles is T2, where T1 < T2 < 250℃.

2. The nano-copper conductive ink according to claim 1, characterized in that, The dispersant is polyvinylpyrrolidone.

3. The nano-copper conductive ink according to claim 1, characterized in that, The solvent comprises at least one of ethanol, ethylene glycol, and water.

4. The nano-copper conductive ink according to claim 1, characterized in that, The antioxidant includes ascorbic acid.

5. The method for preparing nano-copper conductive ink according to any one of claims 1-4, characterized in that, The process includes the following steps: adding the nano-copper particles and dispersant to the solvent, stirring until homogeneous, then adding the repair particles, ultrasonically treating for 10-20 minutes, adding the antioxidant, continuing to stir until homogeneous, and allowing to stand to obtain the nano-copper conductive ink.

6. The application of the nano-copper conductive ink according to any one of claims 1-4, characterized in that, The process includes the following steps: printing the nano-copper conductive ink onto a substrate to form a conductive film, sintering it at T1-T2 for 5-10 minutes under an inert atmosphere, and then continuing to sinter at 20-40°C above T2 for 10-20 minutes.

Citation Information

Patent Citations

  • Anti-oxidative nano-copper conductive ink, and preparation method and printing application

    CN106366769A

  • Nano-copper conductive ink capable of being sintered at low temperature, as well as preparation method and printing application

    CN106928775A

  • Methods of manufacturing conductive composite inks or pastes using mixing zinc particles and tin-based NANO particles

    KR1020130142716A